Zinc Supplementation and Recurrent Diarrhea in Children in Primary Health Care - Masta Hutasoit (Alma Ata University Press, 2020)
ABSTRACT The high rate of infant morbidity and mortality due to diarrhea is still a focus on children's health. In addition to Oral Rehydration Salt (ORS), zinc is a supplement needed to treat diarrhea. As long as the child has diarrhea, the body will lose zinc, so that additional zinc is needed to accelerate the healing process of diarrhea. Zinc is an important micronutrient in the growth of children and is able to prevent diarrhea 2-3 months after diarrhea. The previous study showed that most mothers do not give zinc to diarrhea children (59.3 %), thus there are still many recurrent diarrhea in children. Objective of study to determine the relationship between zinc supplementation in children with diarrhea and the incidence of recurrent diarrhea at Kasihan Primary Health Care, Bantul. We used descriptive correlational with a retrospective approach. The number of respondents was 47 children under five years (0-59 months) with diarrhea who were taken to primary health care and received zinc therapy. The sampling technique was carried out by purposive sampling. Data collection was performed by filling out the questionnaire by visiting the respondent's house (home visit). The result of the contingency coefficient showed p= 0.013 (p < 0.05) which means that there was a statistically significant relationship between zinc supplementation and the incidence of recurrent diarrhea. The closeness of the relationship between the two variables was indicated by the correlation coefficient value of 0.342 which was in a moderate relationship. There is a correlation between giving zinc supplementation to children with recurrent diarrhea in Primary Health Care